Implementing Total Quality Management in a Post-Conflict Educational Context: A Case Study of MSU-Integrated Laboratory School, Philippines - Bunga Citra; Naimah Oranggaga (ADARA, 2026)
This study examines the implementation of Total Quality Management (TQM) at Mindanao State University–Integrated Laboratory School (MSU-ILS) Philippines, as a strategic effort to build sustainable educational quality. MSU-ILS is a laboratory school under the College of Education- Mindanao State University, which plays a dual role as a provider of basic and secondary education and as a training ground for prospective teachers. Employing a qualitative descriptive approach, this research collected data through document analysis, direct observations, and in-depth interviews with school leaders, and teachers to obtain a comprehensive understanding of quality management practices. The findings reveal that MSU-ILS applies TQM principles in an integrated manner through a clear institutional vision, student-centered educational services, continuous improvement initiatives, quality-oriented leadership, and strong collaboration among internal and external stakeholders. These practices are embedded in academic programs, character education, peace education, and organizational culture, supporting the development of an inclusive, transformative, and peace-oriented learning environment, particularly within a post-conflict social context. The study demonstrates that successful implementation of TQM in education extends beyond academic achievement to include character formation, innovation, stakeholder engagement, and long-term organizational commitment. This research provides practical insights for educational institutions, especially schools undergoing quality transformation, to adopt TQM principles as a strategic framework for enhancing educational management, institutional effectiveness, and sustainable school development.